Standardized scaling procedures for rating perceived exertion during resistance exercise - Gearhart, R. F.; Goss, F. L.; Lagally, K. M.; Jakicic, J. M.; Gallagher, J.; Robertsson, R. J. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this project was to determine the validity of standardized Borg scale instructions and scale anchoring procedures to measure active muscle rating of perceived exertion and overall rating of perceived exertion during resistance exercise. Anchoring procedures were determined for each of 7 exercises before the completion of 2 counterbalanced experimental trials. In one trial, subjects lifted 90% of 1 repetition maximum (1RM) 5 times. In the other, subjects lifted 30% of 1RM 15 times. Adjusted R2 and SEMs were used to determine linearity of Borg 15-category scale responses with respect to repetitions at equal work increments for both the group and the sum of the individuals. Both group and individual responses had high adjusted R2 and low SEM values. These results suggest that the current scaling instructions used with the Borg 15-category scale are valid for use during resistance exercise.